Patient-reported outcome measures for post-COVID-19 condition: a systematic review of instruments and measurement properties - Christian Apfelbacher; Christine Blome; Katharina Piontek; Ann-Kristin Baalmann; Theresa Donhauser; Nina Stoletzki (BMJ Open)
Objectives Post-COVID-19 condition (PCC), also referred to as Long COVID, has become an emerging public health issue requiring adequate prevention, treatment and management strategies. Evaluating these strategies from the patients’ perspective using patient-reported outcome measures (PROMs) is critical. In this systematic review, we aimed to critically appraise and summarise the quality of existing PROMs for PCC, and to identify PROMs that can be recommended for use in future research.Design Systematic review using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) methodology.Data sources PubMed and Web of Science were searched on 16 January 2023 and again on 23 July 2024.Eligibility criteria We included studies reporting on the development and/or validation of any disease-specific PROMs for PCC.Data extraction and synthesis Two independent reviewers screened the results for eligibility. The methodological quality of each included study was assessed using the COSMIN Risk of Bias Checklist. We further evaluated the quality of measurement properties per PROM and study according to the criteria for good measurement properties as outlined in the COSMIN manual, and graded the evidence of the synthesised results. Based on the overall evidence, we derived recommendations for the use of the identified instruments.Results We identified 23 studies reporting on 11 PROMs measuring functional status (COVID-19 Yorkshire Rehabilitation Scale, C19-YRS; Modified COVID-19 Yorkshire Rehabilitation Scale, C19-YRSm; Functional Impairment Checklist, FIC; Post-COVID-19 Functional Status Scale, PCFS), symptom burden and impact (Long COVID Symptom and Severity Score, LC-SSS; Long COVID Symptom Tool, LCST; Long COVID Impact Tool, LCIT; Symptom Burden Questionnaire Long COVID, SBQ-LC), quality of life (Post-acute COVID-19 Quality of Life instrument, PAC-19QoL) and stigma (Long COVID Stigma Scale, LCSS; Post-COVID-19 Condition Stigma Questionnaire, PCCSQ). Sample sizes of the included studies ranged from 29 to 1969 participants. Overall, 95 single studies on measurement properties were evaluated. Among the identified instruments, the Long Covid Stigma Scale (LCSS) showed sufficient content validity and internal consistency and can be recommended for use according to COSMIN criteria. Our assessment of measurement properties revealed significant evidence gaps for all PROMs, indicating the need for further validation studies to make an adequate decision on the recommendation for their use. Content validity is a major shortcoming of all included instruments.Conclusion The LCSS measuring stigma can be recommended for use in future research. For the assessment of PCC symptoms and impact, no instrument with sufficient measurement properties is currently available. Further validation of all identified PROMs is indicated, in particular comprehensive assessments of content validity involving experts and patients.PROSPERO registration number CRD42023391238.